2016
DOI: 10.4238/gmr15048630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fragmentation on the natural genetic diversity of Theobroma speciosum Willd. ex Spreng. populations

Abstract: ABSTRACT. Forest fragmentation reduces the effective size of natural populations, isolates individuals in the landscape, and, consequently, changes species' mating systems by increasing the degree of relatedness between individuals and inbreeding. Investigating the impact of habitat degradation on forest fragments helps to assess the genetic and ecological consequences of these changes, and allows the development of effective and sustainable conservation strategies to manage the genetic resources of species li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
1
5
1
2
Order By: Relevance
“…The observed heterozygosity in the three G. americana populations was lower than the expected heterozygosity. Similar results have been found in several studies conducted with tropical species (Silvaet al, 2017;Dardengoet al, 2016;Varella et al 2016). According to Alves et al (2007), the number of alleles is correlated with the expected heterozygosity value.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed heterozygosity in the three G. americana populations was lower than the expected heterozygosity. Similar results have been found in several studies conducted with tropical species (Silvaet al, 2017;Dardengoet al, 2016;Varella et al 2016). According to Alves et al (2007), the number of alleles is correlated with the expected heterozygosity value.…”
Section: Discussionsupporting
confidence: 91%
“…It showed that the three original populations share genetic material and that the genetic diversity is not geographically structured in the individuals belonging to these populations. Studies about Amazon species such as Maurita flexuosa, Theobroma speciosum and Spondias mombin showed that the genetic diversity was geographically structured (Silva et al, 2017;Varella et al, 2016;Rossi et al, 2014), unlike what we observed.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…De acordo com Varella et al (2016), com base em observações de campo, a dispersão das sementes T. speciosum é realizada principalmente por macacos, que ao se alimentarem dos frutos deixam cair as sementes próximas da árvore mãe. Esse padrão de dispersão, aliado ao sistema reprodutivo da espécie que é autoincompatível (SOUZA & VENTURIERI, 2010), gera um agrupamento maior de indivíduos aparentados e aumenta a possibilidade de cruzamentos entre indivíduos da mesma família.…”
Section: Discussionunclassified
“…Além disso, com as sementes (amêndoas) pode-se preparar chocolate (ROSSI et al, 2017). Diante disso, a espécie pode atuar como fonte de renda para as comunidades nativas, promover o desenvolvimento regional e incentivar o uso racional e conservação dos recursos genéticos existentes (VARELLA et al, 2016).…”
Section: Introductionunclassified